Dabartinės latvių kalbos priegaidės ir jų akustiniai požymiai (trukmė, intensyvumas, pagrindinis tonas, kokybė) - Kudirka, Robertas (Baltistica, 2004)
ACOUSTIC CHARACTERISTICS OF SYLLABLE INTONATIONS IN THE MODERN LATVIAN LANGUAGE The article aims to describe the acoustic features of the accented monophthongs and also to discover the differences between the circumflex (Latv. stieptā) and acute (Latv. krītošā) intonations. The author investigated words in the literary language which have the monophthong, CV type, accented on the first syllable. The analysis of the spectrograms was based on the description and investigation of the attributes of the monophthongs: fundamental frequency, intensity, duration, and fundamental formants. Conclusions of experiment: Circumflex vowels more often are characterized by the greatest relative duration, whereas vowels with the acute intonation are shorter. The analysis of parameters of the fundamental frequency testifies to the fact that the circumflex vowels compared to vowels with the acute intonation differ by having a narrower range, shorter maximal length and by the later occurrence of high pitch. Systematical and statistically important differences of ranges show various changes of the contour of fundamental frequency: the fundamental frequency of circumflex vowels changes in regular intervals and not sharply, and the initial fundamental frequency of acute intonation vowels is higher than the circumflex. However the fundamental frequency is lowered too more sharply than in the circumflex vowels. Intonations differ in intensity: the curve of intensity of circumflex vowels changes smoothly; the range of change is narrow; the top of the intensity occurs later; the curve of intensity in acute intonation vowels falls sharply, therefore changes of ranges of acute intonation vowels are wide. The structure of the formants doesn’t depend on the type of intonation.